Tissue-engineered arterial intima model exposed to steady wall shear stresses. (5th March 2021) - Ben-Saadon, Sara; Gavriel, Mark; Zaretsky, Uri; Jaffa, Ariel J.; Grisaru, Dan; Elad, David
Abstract: The arterial intima is continuously under pulsatile wall shear stresses (WSS) imposed by the circulating blood. The knowledge of the contribution of smooth muscle cells (SMC) to the response of endothelial cell (EC) to WSS is still incomplete. We developed a co-culture model of EC on top of SMC that mimics the inner in vivo structure of the arterial intima of large arteries. The co-cultured model, as well as a monolayer model of EC, were developed in custom-designed wells that allowed for mechanobiology experiments. Both the monolayer and co-culture models were exposed to steady flow induced WSS of up to 24 dyne/cm 2 and for lengths of 60 min. Quantification of WSS induced alterations in the cytoskeletal actin filaments (F-actin) and vascular endothelial cadherin (VE-cadherin) junctions were utilized from confocal images and flow cytometry. High confluency of both models was observed even after exposure to the high WSS. The quantitive analysis revealed larger post WSS amounts of EC F-actin polymerization in the monolayer, which may be explained by the relative help of the SMC to resist the external load of WSS. The VE-cadherin demonstrated morphological alterations in the monolayer model, but without significant changes in their content. The SMC in the co-culture maintained their contractile phenotype post high WSS which is more physiological, but not post low WSS. Generally, the results of this work demonstrate the active role of SMC in the intima performance to resist flow induced WSS.